2018
DOI: 10.1093/infdis/jiy269
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Ebola and Marburg Viruses Is Associated With Differential Activation of the Myeloid Compartment in Humanized Triple Knockout-Bone Marrow, Liver, and Thymus Mice

Abstract: Ebola virus (EBOV) and Marburg virus (MARV) outbreaks are highly lethal, and infection results in a hemorrhagic fever with complex etiology. These zoonotic viruses dysregulate the immune system to cause disease, in part by replicating within myeloid cells that would normally innately control viral infection and shape the adaptive immune response. We used triple knockout (TKO)-bone marrow, liver, thymus (BLT) humanized mice to recapitulate the early in vivo human immune response to filovirus infection. Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Interestingly, the data suggested human donor-specific variations on the outcome of the disease [40], which should be considered in conjunction with the possible effects of engraftment efficiency, as was shown in hu-NSG-A2 mice [38]. In addition, flow cytometry analysis of human cells in EBOV-infected BLT humanized C57BL/6 Rag2 −/− Il2rG c −/− Cd47 −/− (TKO-BLT) mice [41], ≈60% of which succumbed to infection by 22 days post-infection (dpi), suggested that EBOV infection induced myeloid cell dysfunction and skewing of macrophage subsets in vivo at late time points, in line with prior in vitro experiments using human cells [54,55].…”
Section: Ebolavirusesmentioning
confidence: 78%
See 4 more Smart Citations
“…Interestingly, the data suggested human donor-specific variations on the outcome of the disease [40], which should be considered in conjunction with the possible effects of engraftment efficiency, as was shown in hu-NSG-A2 mice [38]. In addition, flow cytometry analysis of human cells in EBOV-infected BLT humanized C57BL/6 Rag2 −/− Il2rG c −/− Cd47 −/− (TKO-BLT) mice [41], ≈60% of which succumbed to infection by 22 days post-infection (dpi), suggested that EBOV infection induced myeloid cell dysfunction and skewing of macrophage subsets in vivo at late time points, in line with prior in vitro experiments using human cells [54,55].…”
Section: Ebolavirusesmentioning
confidence: 78%
“…Studies of MARV infection in HIS mice are much more limited than ebolavirus studies. Only one report, using the TKO-BLT model, investigated MARV infection in HIS mice [41]. In humans, MARV disease is comparable in severity to EBOV disease.…”
Section: Marvmentioning
confidence: 99%
See 3 more Smart Citations